Rapid Detection of Bifidobacterium bifidum in Feces Sample by Highly Sensitive Quartz Crystal Microbalance Immunosensor - Hou, Kaijian; Zhao, Pingsen; Chen, Yongru; Li, Guiping; Lin, Yu; Chen, Danjie; Zhu, Dan; Wu, Zezhen; Lian, Danchun; Huang, Xiaojun; Li, Jilin (Frontiers in Chemistry, 2020)
In this work, a quartz crystal microbalance (QCM) sensor has been fabricated using immunoassay for sensitive determination of Bifidobacterium bifidum. Au nanoparticle has been used for amplifying sandwich assays. The proposed immunosensor exhibited a linear detection range between 103–105 CFU/mL with a limit of detection of 2.1×102 CFU/mL. The proposed immunosensor exhibited good selectivity for B. bifidum sensing with low cross reactivity for other foodborne pathogens such as Lactobacillus acidophilus, Listeria monocytogenes and Escherichia coli. In addition, the proposed immunosensor has been successfully used for B. bifidum detection in feces samples and food samples. The frequency decreases of 12, 17, and 10 Hz were observed from the milk samples consisting of the mixtures of Lactobacillus acidophilus, Listeria monocytogenes and Escherichia coli. The frequency decreases of 8, 15, and 7 Hz were observed from the feces samples consisting of the mixtures of Lactobacillus acidophilus, Listeria monocytogenes and Escherichia coli.